Potential effects of stress in critical illness through the role of stress neuropeptides - Papathanassoglou, Elizabeth; Giannakopoulou, Margarita; Mpouzika, Meropi (My University, 2010)
AIMS AND OBJECTIVES: To critically review evidence on the hypothesis that the multitude of cognitive and psychological stressors perceived by critically ill individuals may contribute to the development of pathophysiologic sequlae through modulation of the levels of stress neuropeptides. BACKGROUND: Critically ill individuals experience high levels of stress and intense adverse emotions. Although psychological stress has long been recognized as a factor in disease, and despite the nursing tenet on the importance of patients' psychological responses, in critical care, the potential physiologic effects of stress have received little attention. DESIGN, METHODS: Narrative critical review. Databases searched included Medline, CINAHL, PubMed and the Cochrane Library. Evidence on the role of stress neuropeptides and pertinent findings in critically ill individuals are reviewed. RESULTS: Limbic and extra-limbic brain structures along with specific stress neuropeptides [corticotrophin releasing hormone (CRH), adrenocorticotropin hormone (ACTH), neuropeptide Y , vasopressin, prolactin, oxytocin, substance P, cholecystokinin, endorphins, enkephalins, somatostatin, noradrenaline, melatonin] are involved in emotional and stress responses. Research evidence indicates that stress neuropeptide levels may be altered in critical illness. Moreover, they mediate processes such as immunity, endothelial response and oxidative stress. A framework for future research and practice is presented. CONCLUSIONS: It is probable that, in critical illness, psychological stress accentuates pathophysiological sequlae, through release of neuropeptides. The role of neuropeptides is suggested as an important field of investigation for critical care nursing. However, currently available data are insufficient to draw firm conclusions. Focussed studies on the physiologic correlates of psychological stress in the critically ill are needed. RELEVANCE TO CLINICAL PRACTICE: If this hypothesis is corroborated, bedside quantification of selected neuropeptides may contribute to the assessment of stress and of the effectiveness of psychological support interventions in the future. Moreover, psychosocial and, probably, pharmacological support interventions may be effective adjuncts to the care of the critically ill
Keywords: Sleep; Intensive Care Units; Sound levels